Education of Sociality in Small Communities (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Sociality in small communities leads to accrued social capital of bonding, bridging and linking. Education of community members’ sociality increases bonding, bridging and linking social capital of the community. Research aim of this study was to reveal the links between activity of community groups and community bonding, bridging and linking social capital. Research methods. The subjects flled in the questionnaire based on the research of F. J. Elgar et al. (2011). The sociality was associated with community social capital, namely its components of bonding social capital, bridging social capital and linking social capital. The subjects were asked to evaluate the items using Likert type 5 point scale. The participants were divided into two groups: engaged in community activities (240 people, among them 35% males and 65% females, mean age 48.52 years) and not engaged in activities (262 people, 62.6% females and 37.4% males, mean age 46.97 years). Research results. The estimates of both groups on bonding social capital scale were not statistically signifcant (p > 0.05). Statistically signifcant differences were found assessing the bridging social capital (p < 0.05; t = 4.56), and linking social capital (p < 0.05; t = 3.17) in both groups. Checking the differences of opinions between both groups of men – men and women – women showed statistically signifcant differences only for women’s bridging social capital (p < 0.05; t = 88.19) and linking social capital (p < 0.05; t = 4.01). Discussion and conclusions.The data confrmed the hypothesis that bridging and linking social capital was related to community engagement. The engaged participants indicated higher levels of bridging and linking social capital. Keywords: community, sociality, bonding social capital, bridging social capital, linking social capital.